2020
DOI: 10.1007/s00586-020-06303-z
|View full text |Cite
|
Sign up to set email alerts
|

Prone single-position extreme lateral interbody fusion (Pro-XLIF): preliminary results

Abstract: Background Single-position options for combined anterior and posterior fusion in the lumbar spine have been suggested to reduce the surgical time and improve the efficiency of operating room. Previous reports have focused on lateral decubitus single-position surgery. The goal of this study is to describe and evaluate the feasibility and safety of prone single-position extreme lateral interbody fusion (XLIF) with posterior fixation. Methods Design Pilot prospective non-randomized controlled study. Seven patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 19 publications
6
61
0
Order By: Relevance
“…However, comparatively, we did not experience any episodes of intraoperative cage subsidence. While we did not evaluate surgical outcomes in the current study, we did note a rate of postoperative hip pain that was similar to that published by Lamartina and Berjano, 20 which appeared similarly transient. Overall, we agree that such prone positioning presents an attractive option for streamlined surgical solutions.…”
Section: Discussionsupporting
confidence: 76%
“…However, comparatively, we did not experience any episodes of intraoperative cage subsidence. While we did not evaluate surgical outcomes in the current study, we did note a rate of postoperative hip pain that was similar to that published by Lamartina and Berjano, 20 which appeared similarly transient. Overall, we agree that such prone positioning presents an attractive option for streamlined surgical solutions.…”
Section: Discussionsupporting
confidence: 76%
“…Whether prone LLIF results in possibly less neurologic complications due to the relatively increased safe working at L4-L5, or more neurologic complications due to increased tension on the lumbar plexus has yet to be determined in clinical studies. 17,29 Previous retrospective studies assessing prone LLIF have reported a neurologic complication rate ranging from 37% to 57%, [16][17][18] which ranges within the neurologic complication rate associated with traditional lateral decubitus LLIF. [30][31][32][33][34] One prospective, non-randomized, comparative study assessed seven patients undergoing prone LLIF and ten patients undergoing traditional lateral decubitus LLIF.…”
Section: Discussionmentioning
confidence: 99%
“…6 Lamartina introduced the feasibility of conducting the extreme lateral interbody fusion with posterior fixation in the prone position. 14 This study outlined a reduced mean surgical time of 133.8 ± 26.6 minutes in the prone position, as compared to 182.8 ± 47.9 minutes in standard lateral decubitus. Walker et al 15 report a similar lengthened mean surgical time of 203.6 ± 64.8 minutes in standard lateral decubitus, as well as similar rates of known complications.…”
Section: Discussionmentioning
confidence: 84%
“…Walker et al 15 report a similar lengthened mean surgical time of 203.6 ± 64.8 minutes in standard lateral decubitus, as well as similar rates of known complications. 14…”
Section: Discussionmentioning
confidence: 99%